THE EXPERT BOARD'S ABSTRACT ON QUESTIONS OF THE SURVIVAL OF BIOLOGICAL AGENTS AND THE POSSIBILITY OF SWITCHING TO SECUKINUMAB IN ANKYLOSING SPONDYLITIS IN REAL CLINICAL PRACTICE - artilce Editorial (Научно-практическая ревматология, 2017)
.